Association between family poverty income ratio and Parkinson’s disease in adults aged 40 and older: a study from NHANES 2003–2020 - Li, Cheng; Huang, Jun; Zhang, Yemin (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease (PD) is a prevalent neurodegenerative condition that has significant effects on public health. This study examines the relationship between the family poverty income ratio (PIR) and the prevalence of PD among American adults aged ≥40 years.MethodsThis study leverages data from eight consecutive cycles (2003–2004 to 2017–2020) of the National Health and Nutrition Examination Survey (NHANES), a nationally representative cross-sectional surveillance program that employs stratified multistage probability sampling. The analytical cohort comprises 30,039 U.S. adults aged ≥40 years after applying exclusion criteria. To investigate the relationships between PD, PIR, and other covariates, weighted univariable logistic regression is utilized. The association between PIR and PD is then further assessed using weighted multivariable logistic regression. The possible linear or nonlinear character of this association is investigated using smoothed curve fitting. To evaluate the consistency of the association between PIR and PD across different clinical and demographic subgroups, subgroup analyses are conducted.ResultsA total of the 30,039 participants in the study, 14,743 are men (49.08%) and 15,296 are women (50.92%). With an odds ratio of 0.83 (95% confidence interval: 0.75–0.91, p = 0.0003), PIR was found to be negatively associated with PD after controlling for all other variables. Subgroup analyses are stratified by gender, marital status, body mass index, diabetes, hypertension, stroke, and smoking status. These analyses reveal no statistically significant inverse association between the PIR and PD. However, race, age, and educational attainment exhibit significant interaction effects (p for interaction < 0.05), suggesting these variables may influence the PIR-PD relationship.ConclusionAmong American adults aged ≥40, this study shows a significant inverse relationship between PIR and the prevalence of PD. The results highlight how socioeconomic status may have an impact on the emergence of neurodegenerative diseases. To fully understand the intricate relationship between socioeconomic factors and PD, more extensive prospective studies are necessary.